Supporting Fieldwork Learning by Visual Documentation and Reflection - Saltofte, Margit (Acta Paedagogica Vilnensia, 2017)
Photos can be used as supplements to written fieldnotes and as sources for mediating reflection during fieldwork and analysis. As part of a field diary, photos can support the recall of experiences and a reflective distance to the events. Photography, as visual representation, can also lead to reflection on learning and knowledge production in the process of learning how to conduct fieldwork. Pictures can open the way for abstractions and hidden knowledge, which might otherwise be difficult to formulate in words. However, writing and written field notes cannot be fully replaced by photos and visual images. Techno-anthropology students at Aalborg University, in their course titled “Portfolio in Anthropological Work,” use photography and visual abstractions for different purposes during fieldwork. This article analyzes certain excerpts from students’ portfolio works in order to show the role played by photos in their learning process. For students, photography is an everyday documentation form that can support their memory of field experience and serve as a vehicle for the analysis of data. The article discusses how photos and visual representations support fieldwork learning and analysis based on students’ initiatives and experience in using photos and photographing for a wide aspect of purposes during participant-observation.
Keywords: fieldwork learning; photos; visual reflection; learning portfolio